Enhancing Critical Thinking Skills Through Project Based Learning Among High School Learners - Gusma Afriani; Zuhri Zuhri (Global Education Journal, 2025)
In today’s rapidly changing world, developing critical thinking skills has become a vital educational goal, yet traditional teacher-centered methods often fail to nurture students’ analytical and reflective abilities. This study aims to explore how Project Based Learning (PBL) enhances critical thinking among high school learners through authentic inquiry, collaboration, and reflection. Employing a qualitative approach, the research was conducted over three months at a public high school in Indonesia, involving one teacher and twenty-four students. Data were collected through classroom observations, semi-structured interviews, document analysis, and student reflections, and analyzed using the Miles and Huberman interactive model. The findings reveal that PBL effectively fosters students’ reasoning, problem-solving, and metacognitive awareness by engaging them in real-world projects that demand evaluation, justification, and evidence-based decision-making. Collaborative learning and teacher facilitation were found to play a crucial role in stimulating dialogue, curiosity, and reflective judgment. The study concludes that PBL provides a meaningful alternative to conventional instruction by transforming students from passive learners into active thinkers. Its contribution lies in offering empirical and pedagogical insights into how inquiry-driven learning environments can cultivate critical and independent minds, preparing students for lifelong learning and responsible citizenship.